+0  
 
0
75
4
avatar+105 

Suppose f is a polynomial such that f(0) = 47, f(1) = 32, f(2) = -13, and f(3)=16. What is the sum of the coefficients of f?

 Aug 8, 2021
 #1
avatar
0

The sum of the coefficients is f(1) - f(0) = 32 - 47 = -15.

 Aug 8, 2021
 #2
avatar+105 
+1

I don't quite understand how you got to this? Can you explain?

QuestionableBean  Aug 8, 2021
 #3
avatar+34388 
+3

Here is how that works

    suppose polynomial is   3x ^2 + 2x -4      when x = 0: 

                                            0   +   0  - 4                     then when x = 1 :

                                            3   +   2   -4                        now subtract    when x = 0 from when x =1

                                              3 + 2 -4    -   -4   = 3+2 = 5       which is the sum of the coefficients !

ElectricPavlov  Aug 8, 2021
 #4
avatar+105 
0

Oh thank you!

QuestionableBean  Aug 8, 2021

44 Online Users

avatar